Systems approach to economic risk analysis of Bos taurus beef embryo transfer programs through stochastic simulation - Aherin, Dustin Grant (Kansas State University, 2017)
The dynamic environments, varying production practices, and general biological uncertainty associated with bovine reproduction makes informed, strategic decision making regarding the implementation of bovine reproductive technology a great challenge for producers. One might also argue that traditionally, ET’s primary focus of genetic improvement has greatly overshadowed any consideration of short to mid-term financial gain. To accomplish the objective of creating an economic risk analysis tool for user-defined embryo transfer (ET) programs, a circumstantial, stochastic prediction model utilizing @Risk© software to generate comparable economic values as an aid in the ET decision making process has been created. More realistic than the use of means in deterministic models, distributions defining the biological uncertainty for a multitude of reproductive outcomes are estimated through extensive literature review and limited industry sources. Applying the Latin Hypercube variation of Monte Carlo simulation, a sample value from the descriptive distribution associated with each stochastic variable is included in an iteration of the simulation. Through large numbers of iterations with dynamic combinations of variables, the process culminates in a distribution of possible values for the net present value (NPV), annuity equivalent net present value (ANPV), and return on investment (ROI) associated with the model described scenario of in-vivo derived (IVD) or in-vitro produced (IVP). Finally, using the distributions of NPV, ANPV, and ROI a decision maker can assess the economic risk linked to a user-defined ET program. To further complicate matters, cattle producers are now presented with a choice between two primary methods of ET. IVD ET describes the traditional method of ET that involves follicular stimulation and insemination of a donor female followed by the collection of fertilized embryos from the uterus. IVP commonly refers to the method of generating transferable embryos by collecting oocytes by ovarian aspiration; in-vitro fertilization of the collected oocytes; and incubated maturation of the fertilized oocytes. Encompassed within the two methods of ET exist several different sub-techniques, principally regarding the exception or inclusion of follicular synchronization and/or stimulation before ovum pick-up (OPU) in IVP procedures. Ultimately, operators must decide whether ET programs, of any type, serve as an economically viable means to increase rate of genetic improvement or take advantage of marketing opportunities. Although several economic value predictors for ET programs already exist (Beltrame et al. 2010), the opportunity remains to create more applicable models for Bos taurus beef production and varying marketing avenues in the U.S. This circumstantial, stochastic simulation model can serve as an aid in the ET decision making process by generating output that allows for the financial risk and sensitivity analysis of a user-defined ET program.
Keywords: Stochastic modeling; Embryo transfer; Beef cattle; Investment analysis; Economic risk; Simulation